Postoperative anemia and early functional outcomes after fast‐track hip arthroplasty: a prospective cohort study. Issue 4 (4th March 2016) - Jans, Øivind; Bandholm, Thomas; Kurbegovic, Sorel; Solgaard, Søren; Kjærsgaard‐Andersen, Per; Johansson, Pär I.; Kehlet, Henrik
Abstract : BACKGROUND: Postoperative anemia is prevalent in fast‐track hip arthroplasty (THA) where patients are mobilized and discharged early, but whether anemia impairs functional recovery after discharge has not been adequately evaluated previously. This study aimed to evaluate whether postoperative anemia influenced recovery of mobility and quality of life (Qol) during the first 2 weeks after discharge from THA. STUDY DESIGN AND METHODS: This was a prospective observational study in 122 THA patients more than 65 years of age. Mobility and Qol were assessed pre‐ and postoperatively by the 6‐minute walk test (6MWT; primary outcome), the timed up‐and‐go test, and the FACT‐anemia subscale. Twenty‐four‐hour mobility at home was assessed by activity monitoring on Days 1 to 6 after discharge. Hemoglobin (Hb) at discharge (HbD) and the Hb decrease from preoperatively (ΔHb) were compared to mobility and Qol the first 2 weeks after discharge using bivariate and multivariate linear regression. RESULTS: Mean (±SD) HbD and ΔHb values were 11.1 (±1.4) and 2.8 (±1.2) g/dL and correlated weakly to 6MWT 2 weeks after discharge (r = 0.23 and r = −0.20 respectively; p < 0.05) but HbD levels were not correlated to other mobility or Qol measures. After adjustment for preoperative patient‐related factors, HbD explained 6% (95% confidence interval, 0%‐9%; p < 0.05) of the variation in 6MWT recovery. CONCLUSION: Despite a weak, but significant, correlation between postoperative Hb and the recovery of 6MWT, all other mobility and Qol measures were not influenced by postoperative Hb. Thus, moderate postoperative anemia has limited impact on early postdischarge functional recovery after fast‐track THA.